PEMBENTUKAN DAN PENDAMPINGAN KELOMPOK PEMBUDIDAYA IKAN (POKDAKAN) UNTUK PENGUATAN EKONOMI MASYARAKAT DESA SUMBEREJO KABUPATEN SITUBONDO JAWA TIMUR - Ach. Khumaidi; Abdul Muqsith; Abdul Wafi; Musyaffa Rafiqie; Dimas Galang Prakosa; Ach. Dhofyun Nufur; Moh. Shahibussa’ Dayki (LP2M Universitas Ibrahimy, 2024)
In order to strengthen the economy of the community in Sumberejo Village and overcome the limited stock to supply catfish, it is necessary to form a community business, namely a catfish cultivator group. There were twelve potential community members were gathered to be taught and assisted in the process of establishing and managing a catfish cultivation business. The members of the community were taught technically how to cultivate catfish right through to the marketing process, then facilitated the formation of farmer groups together with the Situbondo district fisheries instructor and the Sumberejo Village Head until the